2008
DOI: 10.1136/gut.2008.156695
|View full text |Cite
|
Sign up to set email alerts
|

A high incidence of MSH6 mutations in Amsterdam criteria II-negative families tested in a diagnostic setting

Abstract: There is a high incidence of MSH6 mutations in families tested for Lynch syndrome in a diagnostic setting. Many of these families remain underdiagnosed using the AC II. The rBG are more useful to select these families for further analysis. However, to optimise the detection of MSH6 families, MSI and IHC analysis should also be performed in families with clustering of late-onset endometrial carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 27 publications
1
29
1
Order By: Relevance
“…This increased the sensitivity of the detection of Lynch syndrome to 78% [7]. However, a recent study showed that only 39% of patients with Lynch syndrome fulfilled the Amsterdam II criteria, and only 25% of patients with MSH6 mutations meet Amsterdam II criteria [8].…”
Section: Introductionmentioning
confidence: 97%
“…This increased the sensitivity of the detection of Lynch syndrome to 78% [7]. However, a recent study showed that only 39% of patients with Lynch syndrome fulfilled the Amsterdam II criteria, and only 25% of patients with MSH6 mutations meet Amsterdam II criteria [8].…”
Section: Introductionmentioning
confidence: 97%
“…The complete coding sequence of the MSH6 gene, including intron/exon boundaries up to 25 bases in the intron, was amplified by standard PCR. Amplified fragments were subsequently analyzed for genetic alterations by denaturing gradient gel electrophoresis (DGGE) or by direct sequencing as described [17][18][19]. Unique sequence alterations were confirmed at least once by sequence analysis of an independently generated PCR product.…”
Section: Msh6 Mutation Analysismentioning
confidence: 99%
“…Specifically, MSH6 mutations have been associated with a higher cumulative risk for endometrial cancer with a later age of onset as compared to other mismatch repair gene mutations [1][2][3][4][5], and cancers other than colon and endometrial may account for as much as 50% of cancer reported with MSH6 mutations [6]. Clarifying the efficacy of MSI/IHC in other extra-colonic cancers associated with LS is important, since certain cases of LS are likely to present in a clinically atypical manner.…”
Section: Resultsmentioning
confidence: 99%